Adsorption isotherm studies of BOD, TSS and colour reduction from palm oil mill effluent (POME) using boiler fly ash - Igwe,J.C (2010)
Palm oil is one of the two most important vegetable oils in the world's oil and fats market. The extraction and purification processes generate different kinds of waste generally known as palm oil mill effluent (POME). Earlier studies had indicated the possibility of using boiler fly ash to adsorb impurities and colour in POME treatment. The adsorption treatment of POME using boiler fly ash was further investigated in detail in this work with regards to the reduction of BOD, colour and TSS from palm oil mill effluent. The amount of BOD, colour and TSS adsorbed increased as the weight of the boiler fly ash used was increased. Also, the smaller particle size of 425µm adsorbed more than the 850µm size. Attempts were made to fit the experimental data with the Freundlich, Langmuir and Dubinin-Radushkevich isotherms. The R² values, which ranged from 0.8974-0.9898, 0.8848-0.9824 and 0.6235-0.9101 for Freundlich, Langmuir and Dubinin-Radushkevich isotherms respectively, showed that Freundlich isotherm gave a better fit followed by Langmuir and then Dubinin-Radushkevich isotherm. The sorption trend could be put as BOD > Colour > TSS. The apparent energy of adsorption was found to be 1.25, 0.58 and 0.97 (KJ/mol) for BOD, colour and TSS respectively, showing that sorption process occurs by physiosorption. Therefore, boiler fly ash is capable of reducing BOD, Colour and TSS from POME and hence could be used to develop a good adsorbent for POME treatment.